Self‐Healable Multifunctional Electronic Tattoos Based on Silk and Graphene - Wang, Qi; Ling, Shengjie; Liang, Xiaoping; Wang, Huimin; Lu, Haojie; Zhang, Yingying (Advanced functional materials, 2019)
Electronic tattoos (E‐tattoos), which can be intimately mounted on human skin for noninvasive and high‐fidelity sensing, have attracted the attention of researchers in the field of wearable electronics. However, fabricating E‐tattoos that are capable of self‐healing and sensing multistimuli, similar to the inherent attributes of human skin, is still challenging. Herein, a healable and multifunctional E‐tattoo based on a graphene/silk fibroin/Ca2+ (Gr/SF/Ca2+) combination is reported. The highly flexible E‐tattoos are prepared through printing or writing using Gr/SF/Ca2+ suspension. The graphene flakes distributed in the matrix form an electrically conductive path that is responsive to environmental changes, such as strain, humidity, and temperature variations, endowing the E‐tattoo with high sensitivity to multistimuli. The performance of the E‐tattoo is investigated as a strain, humidity, and temperature sensor that shows high sensitivity, a fast response, and long‐term stability. The E‐tattoo is remarkably healed after damage by water because of the reformation of hydrogen and coordination bonds at the fractured interface. The healing efficiency is 100% in only 0.3 s. Finally, as proof of concept, its applications for monitoring of electrocardiograms, breathing, and temperature are shown. Based on its unique properties and superior performance, the Gr/SF/Ca2+ E‐tattoo may be a promising candidate material for epidermal electronics. A self‐healable silk E‐tattoo, which shows high sensitivity to multistimuli including strain/humidity/temperature, is reported. Customer‐designed E‐tattoos can be facilely prepared through screen printing or direct writing of a graphene/silk fibroin/Ca2+ suspension. Remarkably, the E‐tattoo can be healed with an efficiency of 100% even after being fully fractured within 0.3 s simply by a droplet of water.